Peningkatan Etos Kerja Perawat Pelaksana Melalui Pelatihan Self-Leadership - Martha Pitta Uli Marpaung; Dewi Elizadiani Suza; Diah Arruum (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2019)
Self-leadership is a power that is inherent in individuals to influence, direct, control, and push themselves to achieve the desired goals. Self-leadership training is very important to improve work behavior in hospitals. The purpose of this study was to determine the effect of self-leadership training on nurses’ work ethic at the government hospital. The research method uses a quasi-experimental method with nonequivalent control two groups with pre-post test design. The research sample was taken using consecutive sampling with a total of 98 nurses, 49 nurses as the control group and 49 nurses as the intervention group. In the intervention group, self-leadership training was given, whereas the control group was not. The results of the Wilcoxon Signed Ranks test in the intervention group found that there were significant differences in work ethic before and after training (p = 0.00, p˂0.05) while in the control group there were no significant differences in work ethic before and after training (p=0,317, p˃0,05). Spearman's Rho test results showed that there was an effect of self-leadership training on nurses’ work ethic at the government hospital (p = 0.00 <0.05). Self-leadership training can improve nurses’ work ethic at hospitals so it is recommended to conduct training on an ongoing basis to maintain consistency of work ethics in hospitals.